F MARTIS IN MAMMALS FROM NUEVO LEON AND NOTES ON THE SPECIES OF FILARIA - CABALLERO Y C, EDUARDO; C, EDUARDO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1924)
Rhizopod protozoans were not first discovered by Dujardin, as stated by Neveu-Lemaire, but were recorded by numerous authors previously, Hooke first recording foraminiferans, and Rosel von Rosenhof first recording ameboid animals
REV SOC MEX HIST NAT
Keywords: F MARTIS, MAMMALS, NUEVO LEON, NOTES, SPECIES, FILARIA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); ZOOLOGIA GENERAL